Record high thermoelectric performance in bulk SrTiO3 via nano-scale modulation doping. (May 2017) - Wang, Jun; Zhang, Bo-Yu; Kang, Hui-Jun; Li, Yan; Yaer, Xinba; Li, Jing-Feng; Tan, Qing; Zhang, Shuai; Fan, Guo-Hua; Liu, Cheng-Yan; Miao, Lei; Nan, Ding; et al.
Abstract: Strontium titanite (SrTiO3 ), which is an experimentally-friendly thermoelectric material, could be a promising candidate for thermoelectric power generation applications. The theorectical study indicates the co-doping of La and Nb could enhance the thermoelectric performance, however, the thermoelectric figure of merits ( ZT s) of SrTiO3 are still low because the co-doping process at nano-scale is experimentally difficult to control. Here we report a high performance SrTiO3 with La-Nb co-doping, which are prepared by a combination of hydrothermal method and high-efficiency sintering. Nano-scale co-doping is successfully modulated by hydrothermal method, and nano-inclusions precipitate during sintering process, to form complex microstructures. In this case, the electrical and thermal transport properties are optimized simultaneously by doping concentration and dopants type, resulting in a record-high ZT >0.6 at 1000−1100 K in the 10 mol% La and 10 mol% Nb doped SrTiO3 bulk materials. The nano-scale modulation doping and microstructure controlling approach validated in the present study should be also applicable for other thermoelectric materials. Graphical abstract: Highlights: Nb-La-doped SrTiO3 nano powders were successfully synthesized by the hydrothermal method. The nano-inclusions and second phases precipitated from matrix to form a complex micro and electron structure. Record-high ZTs >0.6 at 1000–1100 K were obtained in La-Nb-doped SrTiO3 bulks.